1994
DOI: 10.1002/hep.1840190509
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of calcium salt precipitates in the core, periphery and shell of cholesterol, black pigment and brown pigment gallstones

Abstract: Calcium bilirubinate, palmitate, carbonate and phosphate have been identified in the cores of cholesterol and pigment gallstones, suggesting a role for precipitated calcium salts in the early events of gallstone formation. Previous studies that compared the calcium salt contents of cholesterol and pigment stones required destruction of gallstone structure. We have used scanning electron microscopy with windowless energy-dispersive x-ray microanalysis to determine the prevalence of calcium salts in a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…23, 28 For example, aquaporins likely play an important role in water transport across human gallbladder epithelium. 28 Because higher bile calcium concentrations are a risk factor for pigment gallstones (and also may play a role in the pathogenesis of cholesterol gallstones), 23, 29,30 it is intriguing to consider the possibility of an unknown “channelopathy” that increases calcium content in both bile and urine.…”
Section: Discussionmentioning
confidence: 99%
“…23, 28 For example, aquaporins likely play an important role in water transport across human gallbladder epithelium. 28 Because higher bile calcium concentrations are a risk factor for pigment gallstones (and also may play a role in the pathogenesis of cholesterol gallstones), 23, 29,30 it is intriguing to consider the possibility of an unknown “channelopathy” that increases calcium content in both bile and urine.…”
Section: Discussionmentioning
confidence: 99%
“…The content and distribution of a gallstone's components can provide information on the pathophysiological process of gallstone formation. Because of the limited means of examining gallstones, previous studies could not accurately depict the three‐dimensional spatial distribution of gallstone components (Diehl et al,1995; Kaufman et al,1994; Rautray et al,2006; Schafmayer et al,2006; Wang et al,2010; Yoo et al,2008). In our study, the conflict between positioning analysis and qualitative detection in sample preparation was avoided by using Fourier transform infrared specular reflection spectroscopy combined with micron‐scale microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, 2 (4%) of our adult patients had calcium carbonate stones. In American adults, calcium carbonate is found in small quantities (≤20% weight) in up to 20% of cholesterol and pigment gallstones [10][11][12][13]. These small amounts of calcium carbonate are more frequently found in the peripheral layers of cholesterol gallstones [10,14], supporting the concept that calcium carbonate precipitation more commonly occurs during intermittent obstruction of the cystic duct by a cholesterol stone than at stone nidation.…”
Section: Discussionmentioning
confidence: 85%
“…Kaufman et al [13] found no calcium carbonate gallstones among 146 consecutive adults undergoing cholecystectomy at the Johns Hopkins Hospital, Baltimore, MD. In a previous study of gallbladder stones from 50 adults from Galveston, Texas, all were found to be cholesterol stones; none contained more than 20% calcium carbonate (Soloway and Taylor, unpublished observations).…”
Section: Discussionmentioning
confidence: 98%